The application of microtremor survey method in investigating the geological formation of Singapore - Muhammad Azri Bin Omar. (2011)
In the recent study of seismic activities, the Microtremor Survey Method (MSM) has become a very much interesting tool in estimating subsurface soil structure for better understanding of the ground response by amplification factor. This research has been undertaken by many around the world mainly because of the advantages it offers as oppose to conventional site investigation such as boring. The method is also known to be low in cost and non-destructive in nature.The entire project will plan to investigate the geological formation of Singapore as well as estimating subsurface soil profile using the MSM. Moreover, the Spatial Autocorrelation (SPAC) method will be applied to show how the recorded data will be selected and processed to estimate Rayleigh wave dispersion curve, thereafter estimating the subsurface soil layers. A comparison between the results obtained from SPAC analysis as well as borehole information will also be shown to check for consistency.